ANALISIS PENGARUH PERSEPSI HARGA, KUALITAS PRODUK, DAN KUALITAS PELAYANAN TERHADAP MINAT BELI ULANG KONSUMEN DI SOP BUAH FRESHASAN BANJARSARI SELATAN TEMBALANG - Nashafa, Pamila; Magnadi, Rizal Hari (Faculty of Economics and Business Diponegoro University, 2016)
This research was conducted to analyze the factors that influence the buying interest Freshasan fruit soup products. The number of fruit soup brands make the competition tighter. A company needs to create products that appeal consumers, so consumers will choose a product Freshasan fruit soup. The problems of this study to analyze the influence of the perception of price, product quality, and the quality of the buying interest re waiter to consumers in South Banjarsari Freshasan fruit soup Tembalang. The independent variable in this study consisted of Perception Price, Quality of Products, Quality of Service, and the variable is dipendennya Consumer Buying Interests the fruit soup Freshasan South Banjarsari Tembalang.Sempel totaling 100 respondents taken using probability sampling technique. Analysis using SPSS 16.0 that includes a reliability test, validity test, classic assumption test, multiple regression analysis, hypothesis testing through F test and T, as well as analysis of multiple determination coefficient. From the analysis, regression equation:Variables influence price perceptions Â has positive influence on the buying interest with a coefficient of 0.263. The variable quality of Â product has positive influence on the buying interest with a coefficient of 0.192. Variable quality of service positive influence on the buying interest with a coefficient of 0.391.The model shows that the regression coefficient of all variables are positive. Based on the standardized coefficient of the regression model can be stated that any change in the independent variable, it will cause a change also in dependenny variable. It is seen that Perception of the Price, Quality of Product and Quality of Service positive influence, so it will affect the interest of the consumer in purchasing fruit soup Freshasan South Banjarsari Tembalang.